Unflooding Asia : the green cities way - Vojinović, Zoran; Huang, Jingmin (IWA Publishing, 2014)
A continuing increase in disasters triggered by floods occurs almost daily even though our technological capabilities have grown rapidly and global economic growth per capita has doubled. This paradoxical situation proves that our earlier ways of thinking are inadequate and that we must shift our way of thinking and working. It has become obvious that most flood-related disasters, although commonly referred to as natural disasters, are not the result of nature-related processes alone. Some of the early efforts in dealing with floods and flood-related disasters were only concerned with the construction of engineering structures (e.g., levees, floodwalls, dams, embankments, storage basins, diversions, etc.) without significant consideration of aspects which are nowadays regarded as equally important, if not more important. There is a great deal of natural, social and technological interactions that shape the vulnerability to floods. Realizing that flood risk can hardly ever be completely eliminated, the traditional 'flood defence' culture has been replaced with the culture of learning how to live under flood risk and how to better respond to it. This renders purely engineering solutions inadequate. Can the threats of more flood-related disasters provide an impetus to shift our mind-set towards an approach that favours not only sound technological innovations but one that also addresses the social, cultural, and wider ecological aspects of dealing with floods? In this illustrated book, the Asian Development Bank (ADB)seeks to introduce a holistic thinking in dealing with urban floods by adopting the green cities development approach. Green cities development is a holistic approach which promotes multipurpose (or multifunctional) solutions that are not only technologically and economically efficient, but which are also ecologically sustainable and socially just.